2021
DOI: 10.7150/ijbs.62114
|View full text |Cite
|
Sign up to set email alerts
|

Cyclovirobuxine inhibits the progression of clear cell renal cell carcinoma by suppressing the IGFBP3-AKT/STAT3/MAPK-Snail signalling pathway

Abstract: Of all pathological types of renal cell cancer (RCC), clear cell renal cell carcinoma (ccRCC) has the highest incidence. Cyclovirobuxine (CVB), a triterpenoid alkaloid isolated from Buxus microphylla, exhibits antitumour activity against gastric cancer and breast cancer; however, the mechanism by which CVB inhibits ccRCC remains unclear. The aim of our study was to explore the antitumour effects of CVB on ccRCC and to elucidate its exact mechanism. Cell viability, proliferation, cell cycle distribution, apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Liu et al. showed that IGFBP3 can directly regulate the key molecules of the AKT, EMT, and MAPK signaling pathways, thereby influencing the oncogenesis and development of renal carcinoma 29 . Therefore, according to previous studies, pathway enrichment analysis, WB assays, and IHC staining in this study, it is plausible to suggest that TOX3 up‐regulates IGFBP3 expression level by binding to the CRE site in the promoter of the downstream gene IGFBP3.…”
Section: Discussionmentioning
confidence: 56%
“…Liu et al. showed that IGFBP3 can directly regulate the key molecules of the AKT, EMT, and MAPK signaling pathways, thereby influencing the oncogenesis and development of renal carcinoma 29 . Therefore, according to previous studies, pathway enrichment analysis, WB assays, and IHC staining in this study, it is plausible to suggest that TOX3 up‐regulates IGFBP3 expression level by binding to the CRE site in the promoter of the downstream gene IGFBP3.…”
Section: Discussionmentioning
confidence: 56%
“…Our study shows that CVB-D effectively and long-lastingly relieves PTX-induced thermal hypersensitivity ( Figure 8 ). This finding, in conjunction with recent reports of CVB-D’s promising in vitro and in vivo antiproliferative activities ( Wu et al, 2015 ; Jiang et al, 2020 ; Zhang et al, 2020 ; Zhou et al, 2020 ; Liu et al, 2021 ; Zeng et al, 2021 ), also raises the potential of an application of CVB-D in cancer treatment and chemotherapy: a combination of CVB-D and PTX may offer a promising opportunity to concurrently enhance the anticancer effect of PTX and reduce its unwanted neuropathic symptoms.…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, exposure to cyclovirobuxine significantly decreased levels of p-AKT, p-STAT3, p-JNK, p-P38 and p-ERK. Mechanistic analyses suggested that cyclovirobuxine inhibits RCC cells by blocking the insulin-like growth factor binding protein 3(IGFBP3)-Akt/STAT3/MAPK-Snail pathway [ 32 ]. Ratnayake et al extracted two unique bioactive sesquiterpenes from Tanzanian Phyllanthus engleri , namely englerin A and B [ 48 ].…”
Section: Resultsmentioning
confidence: 99%